Collisionally pumped hybrid soft X-ray laser in Ne-like sulphur - Rocca, Jorge J., author; Sandner, Wolfgang, author; Bortolotto, Fulvia, author; Janulewicz, Karol A., author; Nickles, Peter V., author; Académie des sciences/Éditions scientifiques et médicales Elsevier SAS, publisher (Colorado State University. Libraries, 2000)
We describe an experiment demonstrating XUV amplification following collisional excitation in a capillary discharge plasma irradiated by a picosecond IR laser pulse. Guiding and temporally resolved transmission of the pump laser beam are also demonstrated and analysed. The short pump laser pulse heated rapidly the electrons producing amplification in the 3p1S0-3s1P1 transition of Ne-like sulphur at 60.84 nm. The estimated gain-length product was equal to 6.8, while the beam divergence reached 2.5 mrad for 30 mm capillary. This new, hybridly pumped collisional soft X-ray laser with the transient gain offers anew way towards efficient table-top XUV sources.
Keywords: x-ray lasers; plasma; collisional excitation; hybrid pumping; plasma waveguide; X–UV spectroscopy; capillary discharge